Orpheus: A Voice-Controlled Game to Train Pitch Matching - Li, Jiahui; Gu, Zhenyu (HCI in Games: Serious and Immersive Games, 2021)
Pitch matching is one of the most basic musical skills, but is hard to stick to because of its monotony. To solve this problem, Orpheus, a serious game based on Greek mythology for training pitch matching is proposed. The player needs to act as Orpheus, the main character of the story who is known as “the father of songs”, to use his great power of music to experience the famous love story with Eurydice. The player needs to control Orpheus by singing specific pitches to change his position and action so that Orpheus can complete the tasks and drive the plots. A game prototype was developed with Unity, and a pilot case study was conducted to measure the game experience and assess the game effectiveness. Results showed that players considered Orpheus as challenging but engaging, and they thought Orpheus was better in training pitch matching than the traditional method. In conclusion, Orpheus provides a new training method for pitch matching that is both engaging and effective.